Uji Kekuatan Dinding Batu Bata dengan Spesi yang Bervariasi Menerima Beban Tekan Terpusat - Firmansyah, Revaldo; Karjanto, Adjib; Djatmika, Boedya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Generally, bricks are used as building structural wall materials and dwelling. This study aims to find out the strength of the brick wall pairs when receiving a lumped load of the roof structure of a mixture commonly used by the community is 1 PC: 8 Sand and 1 PC : 10 Sand so as to avoid cracks in the wall due to the roof structure load. This test used  local bricks from Tumpang Malang with Model M-6B 230 mm x 110 mm x 55 mm. Another materials obtained from the building store in Malang City. The testing method used is SNI 03-4166-1996 robust test procedure for compressing red brick. The test method used is SNI 03-4166-1996 about the test procedure of compressive strength of red brick masonry wall. The dimensions of specimens is 75 x 64 cm as much as 3 samples of each thickness variation, where the thickness variation is 3 cm, 4 cm, and 5 cm so that the number of sample objects test all 18 specimens. Further test object tested press using UTM according SNI 03-4166-1996. The result showed that the average compressive strength of brick masonry wall was 1 PC : 8 Sand on variation of thickness of 3 cm, 4 cm, 5 cm, respectively by 8.26 kg/cm2, 7.63 kg/cm2, 7.4 kg/cm2. The average compressive strength of brick masonry wall of 1 PC : 10 Sand on variation in thickness of 3 cm, 4 cm, 5 cm, respectively by 8.11 kg/cm2, 6.91 kg/cm2, 6.46 kg/cm2.